The heart of darkness: Are executive (dys)functions a common factor in aggression behaviors and bullying? - Henostroza Mesones, Fabiola (2024)
This systematic review aims to conduct a comprehensive analysis of research that proposes executive functions (EFs) as a pathway to understanding the individual factors that support aggressive behavior (AB) and, consequently, contribute to the maintenance of bullying dynamics within school contexts. The search for articles was conducted in databases such as Web of Science, Scopus, and PubMed. Specifically, studies were selected that analyzed the contribution of EFs to AB or the role of perpetrator in bullying situations, conducted in the last 10 years with samples ranging from 4 to 12 years of age. The final result of the search yielded 11 articles, through which it was identified that while EFs contribute to the development of aggressive behavior, their impact may vary depending on the subtype of aggression evaluated. Thus, superior or inferior executive performance can translate into differentiated aggression profiles. Additionally, other variables associated with temperament traits, such as Callous Unemotional, contribute to the construction of specific profiles. This reflects the importance of promoting interventions that, on one hand, consider cognitive factors and, on the other, respond to the specific characteristics of the type of aggression displayed by perpetrators. Fifty years after Olweus coined the term "bullying," there are still gaps and questions to be answered.